2014
DOI: 10.1088/0953-4075/47/14/145003
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultraviolet spectra and analysis ofΔn= 0 transitions in highly charged barium

Abstract: Extreme ultraviolet spectra of highly charged barium atoms were produced with an electron beam ion trap (EBIT) and recorded with a flat-field grazing-incidence spectrometer. The spectra were measured in the wavelength range 4 nm-24 nm with the beam energies varying from 700 eV to 30 000 eV. The line identifications were performed with collisional-radiative modeling of the EBIT plasma that provided good quantitative agreement between simulated and measured spectra. In the energy range 700 eV-1750 eV, fifty thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%
“…Wavelength calibration was performed using highly charged neon lines (Ne V-VIII), xenon lines (Xe XLI-XLII), barium lines (Ba XLIII-XLIV), oxygen lines (O V-VI) and iron lines (Fe XXIII-XXIV) [5,7,11,63,64], as described in this section. Neon and carbon dioxide gases were injected into the EBIT as neutral atoms from the gas injection setup described by Fahy et al [2], with the injection pressure normally on the order of 10 −3 Pa. Iron ions were loaded from the MEVVA ion source.…”
Section: Wavelength Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated spectra were compared with measurements to understand the charge-state balance and correctly identify measured lines. This method has been used in previous works to accurately identify emission features from highly charged ions in x-ray and EUV spectral regions (see, e.g., Ralchenko et al (2006Ralchenko et al ( , 2007Ralchenko et al ( , 2011Podpaly et al (2014); Kilbane et al (2014); Reader et al (2014); Silwal et al (2017)). Many of the earlier works also provide a thorough explanation of the calculations which are omitted here.…”
Section: Collisional-radiative Modeling Of the Ebit Plasmamentioning
confidence: 99%
“…Recently, Christopher J. Fontes et al [24] have calculated relativistic distorted-wave collision strengths for all possible ∆n = 0 transitions in the Li, F and Na-like ions with Z in the range 26 ≤ Z ≤ 92 by using improved "top-up" method. Barium atomic spectra have been among the first ones investigated in nearly every Electron Beam Ion Trap (EBIT) because it is used as a dopant in the electron gun cathode; as a result, its spectral lines are present along with the spectra of injected elements [10]. Spectra of Ba in the visible region have also been reported from the Livermore EBIT [11,12].…”
Section: Introductionmentioning
confidence: 99%